Detener la guerra, no justificarla - Tamayo, Luis (Nómadas. Critical Journal of Social and Juridical Science, 2006)
For centuries, the humanity makes war. Different and various wars against anyone. Wars were justified by Saint Agustin and Aquinus and recently by Teresa Santiago. I would like to think that the purpose of the philosophy of the XXI century shouldbeto stop not to justify it. This article explores the myth of Dionysus because in this myth the Greeks explain thenature of war and the way to stop it.